PENGARUH HARGA, WORD OF MOUTH DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA CV. LAGAS JAYA BADUNG - I Komang Arthur Mahendra; I Gde Agung Wira Pertama; Ida Ayu Agung Idawati (Warmadewa Management and Business Journal (WMBJ), 2022)
The purchase decision is an action taken by consumers in choosing a product from several alternative choices. This study entitled â€œThe Influence of Price, Word of Mouth and Service Quality on Product Purchase Decisions at CV. Lagas Jaya Badungâ€. The purpose of this study was to determine and analyze the effect of word of mouth price and service quality on product purchasing decisions on CV. Lagas Jaya Badung both simultaneously and partially. The research data was collected using a questionnaire with a sample of 87 respondents. The research method uses quantitative analysis with multiple linear regression analysis techniques, hypothesis testing (F test and t test). Based on the results of the F test, price, word of mouth, and service quality simultaneously have a significant effect on product purchasing decision on CV. Lagas Jaya Badung. Based on the results of multiple linear regression analysis, the t test found that price, word of mouth and service quality partially have a positive and significant effect on product purchasing decisions on CV. Lagas Jaya Badung